PERTUMBUHAN DAN KADAR KLOROFIL DAUN Acacia mangium PADA LAHAN BEKAS TAMBANG TIMAH DI PULAU BANGKA - Robika Robika; Eka Sari (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2019)
Tin-mined land has sandy characteristics (more than 95%), is very porous, low KTK, acidic pH and nutrient poor. Revegetation programs have been carried out to improve soil fertility using local and exotic species (Acacia mangium). Rapid growth, tolerance to various environmental conditions and high economic value are the reasons for choosing A. mangium as a revegetation plant. This study aims to analyze the growth and chlorophyll content of A. mangium leaves which grow in two locations of tin-mined land (Tanjung Ratu Village and Rebo Village). The results showed that A. mangium which was grown on a younger tin mined land (in Tanjung Ratu Village) showed an increase in root dry weight, root length, number of root nodules, and decreased leaf chlorophyll levels. On older tin mined land (in Rebo Village), root dry weight, root length, and number of root nodules were lower, but chlorophyll content increased. The characters affected can be used to determine the ability of tolerance and adaptation of A. mangium in tin mined land.